(untitled) (Patan Pragya, 2022)
This research article tries to analyse the livelihood impact of the Kulekhani Hydropower project for the local people. From the use of questioner survey method of the sample area population information were captured. This information had analysed through the descriptive and infernal statistical methods by the help of SPSS software for information gathering. After analysis the information through the descriptive statistics shows the positive impact of the KHS-II project for the local people. Like same, the overall statistics of the regression model result is significant in the5% degree of freedom indicate that the project has positive economic impact for the likelihood of the surrounding community people. The research concluded that KHS-II project have positive impact on the likelihood situation to the surrounding community people.